1980
DOI: 10.1111/j.1432-1033.1980.tb04815.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Refined Physical Map and Heterogeneity of Methylation Sites of Papilloma Virus Type 1a DNA

Abstract: The entire genome of human papilloma virus type 1a was cloned in Escherichia coli using the plasmid pBR322 as vector. The integrity and the homogeneity of the viral DNA thus obtained was confirmed by restriction endonucleases analysis. Viral DNA isolated from a single wart was partially methylated at only one out of the four HpaII sites, d(C‐C‐G‐G). Recognition sites for BglI, BglII, PstI and PvuII restriction endonucleases were located on the cloned genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Methylation is not incompatible with extrachromosomal maintenance per se, since there are some viral DNAs which contain methylated sites when maintained in an extrachromosomal state (4,18,33,35,49). For example, certain sites were methylated in Shope papillomavirus (49), Epstein-Barr virus (18,33,35), and human papillomavirus type la (4).…”
Section: Discussionmentioning
confidence: 99%
“…Methylation is not incompatible with extrachromosomal maintenance per se, since there are some viral DNAs which contain methylated sites when maintained in an extrachromosomal state (4,18,33,35,49). For example, certain sites were methylated in Shope papillomavirus (49), Epstein-Barr virus (18,33,35), and human papillomavirus type la (4).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation in HPV was first described nearly 30 years ago (Danos et al, 1980) and its role in carcinogenesis has been studied subsequently. HPV16 and HPV18 are the most thoroughly analyzed virus types, as they represent the high-risk types of HPV.…”
Section: Human Papilloma Virusmentioning
confidence: 99%
“…Reports more than 20 years ago on HPV-1 and the cottontail rabbit papillomavirus suggested that papillomaviruses are targeted by cellular DNA methylation, although limited analytical power, namely methylation-sensitive restriction enzymes, was accepted as the state of the art of that time (9,13,40,47). Research on the methylation of HPVs was extended recently to the high-risk HPV-16 (2,22) by bisulfite modification and DNA sequencing.…”
mentioning
confidence: 99%